PENGGUNAAN IT DALAM PROYEK NEW PRODUCT DEVELOPMENT DI INDONESIA: IDENTIFIKASI FAKTOR PENENTU DAN DAMPAK KINERJA PROYEK - Boy Bayu Idisondjaja; Pepey Riawati Kurnia, M.M.; Siti Nuraisyah Suwanda (Journal of Management and Business Review, 2018)
This research is a research replication of Determinants of IT Usage and New Product Performance by Barczak, Sultan, and Gultink (2007), adapted using the characteristics of different respondents which are medium and large companies in Indonesia. The first purpose of the research is to identify antecedents of the use of IT tools. The second purpose is to further explore the role of IT in building innovative capabilities that generate values for the company. The study used a quantitative approach with a single cross-sectional conclusive design to test eight hypotheses through multiple regression measurements. The eight variables to be tested are divided into two major groups, namely the determinant variable (project risk, existence of a champion, autonomy, innovative climate, IT infrastructure, IT usage depth) and impact of IT usage performance (speed of product launch to market, market performance). The result of the research shows that the variables of IT usage depth, enterprise innovative climate, IT infrastructure, and project risk have a positive and influential relationship therefore determine the use of IT in NPD than other determinant variables. Meanwhile, the impact of IT usage on project performance is affected by the speed of product launch to market with a positive and significant relationship compared to market performance variable. The practicalities of this research, among others, is to provide an alternative action for managers to increase the use of IT in the process of New Product Development (NPD).